2009
DOI: 10.1098/rspb.2009.0168
|View full text |Cite
|
Sign up to set email alerts
|

The role of nocturnal vision in mate choice: females prefer conspicuous males in the European tree frog ( Hyla arborea )

Abstract: Nocturnal frog species rely extensively on vocalization for reproduction. But recent studies provide evidence for an important, though long overlooked, role of visual communication. In many species, calling males exhibit a conspicuous pulsing vocal sac, a signal bearing visually important dynamic components. Here, we investigate female preference for male vocal sac coloration-a question hitherto unexploredand male colour pattern in the European tree frog (Hyla arborea). Under nocturnal conditions, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
138
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 49 publications
(93 reference statements)
4
138
1
Order By: Relevance
“…Traditionally, the low light intensities available in nocturnal environments were believed to preclude color discrimination (Walls, 1942;Ahnelt and Kolb, 2000). Recent studies, however, suggest that nocturnal color vision may be both selectively advantageous for some species and more widespread than previously believed (Kelber and Roth, 2006;Gomez et al, 2009;Müller et al, 2009). Color discrimination at nocturnal light levels may even be adaptive for some mammals.…”
Section: Introductionmentioning
confidence: 96%
“…Traditionally, the low light intensities available in nocturnal environments were believed to preclude color discrimination (Walls, 1942;Ahnelt and Kolb, 2000). Recent studies, however, suggest that nocturnal color vision may be both selectively advantageous for some species and more widespread than previously believed (Kelber and Roth, 2006;Gomez et al, 2009;Müller et al, 2009). Color discrimination at nocturnal light levels may even be adaptive for some mammals.…”
Section: Introductionmentioning
confidence: 96%
“…Females express a strong preference for the complex call (Ryan, 1985;Rand et al, 1992;Ryan and Rand, 2003a). Several studies have shown that visual cues are also used in the courtship behaviors of anurans (Summers et al, 1999;Hödl and Amézquita, 2001;Amézquita and Hödl, 2004;Taylor et al, 2007;Vasquez and Pfennig, 2007;Gomez et al, 2009). As with most anurans, the male túngara frog vocalization is accompanied by a conspicuous, simultaneous inflation of the vocal sac (Pauly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We based our experimental design on the findings of several previous video playback studies in anurans that females attend to characteristics of male vocal sacs, which are inflated concurrently with sound production (Gomez et al, 2009;Richardson et al, 2010;Rosenthal et al, 2004). The large size and rapid inflation of vocal sacs may improve females' abilities to localize potential mates (Preininger et al, 2013;Rosenthal et al, 2004;Taylor et al, 2008).…”
mentioning
confidence: 99%